Antimicrobial, Antioxidant and Anti-inflammation Activities of Fraction and Single Peptides Derived from Mare Milk Protein - Eni Kusumaningtyas; Didik Tulus Subekti; D FL Fitaningtyas (Indonesian Center for Animal Research and Development (ICARD), 2019)
Mare milk protein contains bioactive peptide which beneficial for human and animal health. Peptides in the fraction and single may show different activities. The objectives of the study were to evaluate antimicrobial and anti-inflammation activities of the fraction and single peptide derived from mare milk protein. Antimicrobial assay was conducted by testing antibacterial and antifungal activities of fraction <3 kDa, peptide HPYFYAPELLYYANK, LVNELTEFAK and LANSLTEFAK against Escherichia coli and Candida albicans. Anti-inflammation effect was detected by interleukin 1-β (IL- 1β) and Tumor Necrosis Factor -α (TNF-α) production in mice after administration of Escherichia coli’s lipopolysaccharide (LPS) and combined with fraction or single peptide. The result showed that antibacterial and antifungal of fraction <3 kDa was higher than all of single peptide. This may because of synergistic interaction among peptide in the fraction which increase the activities. Fraction <3 kDa was also able to decrease production of IL-1β and TNF-α better than single peptide indicated its ability to decrease inflammation. Based on the results, antimicrobial and anti-inflammation activities fraction <3 kDa was better than single peptide.